The role of women in improving the welfare of their families to improve their conditions during the COVID-19 pandemic in Indonesia - Hilmiana Hilmianà; Yusuf Iskandar (Cogent Business & Management, 2024)
The study aimed to analyze women's roles in stabilizing their families to improve their conditions during the pandemic. Women have encountered setbacks as they take care of their families in the wake of the pandemic that has adversely affected people's livelihoods. It employs qualitative research methods and a descriptive study design to ascertain the role women play in improving the welfare of their families during the pandemic. It employs online survey questions and virtual interviews to collect data from a sample size of 100 randomly selected women. The study reveals that women play essential roles in enhancing the hygiene and cleanliness of their homes and children throusgh sanitization and regular washing of hands. They also take leadership and headship of the family following the incapacitation of their spouses by the COVID-19 disease; provide for the family's basic needs, and provide psycho-social support as caregivers to their affected and infected family members. There is also a need to assist women struggling to protect the interest of their family and their livelihoods during the pandemic to emancipate them from the hurdles that have for a long time hindered them from realizing improved living standards.
Keywords: Z15; 650; Family condition; women empowerment; pandemic; socio-economic; family welfare